A Concise Review of Polysomnography and Obstructive Sleep Apnea for the Neurophysiologist. Issue 3 (1st March 2023) - Soltis, Marjorie E.; Spector, Andrew R.
Summary: Sleep as an electrical phenomenon in the brain was first recorded in 1875. Over the next 100 years, recordings of sleep evolved into modern-day polysomnography, which includes not only electroencephalography but also combinations of electro-oculography, electromyography, nasal pressure transducers, oronasal airflow monitors, thermistors, respiratory inductance plethysmography, and oximetry. The most common usage of polysomnography is to identify obstructive sleep apnea (OSA). Research has demonstrated that subjects with OSA have distinctive patterns detected by EEG. The evidence indicates that increased slow activity is seen in both sleep and wake for subjects with OSA and that these changes are reversible with treatment. This article reviews normal sleep, changes in sleep that result from OSA, and the effect that treatment of OSA via continuous positive airway pressure therapy has on normalizing the EEG. A review of alternative OSA treatment options is included, although their effects on EEG in OSA patients have not been studied.